2017
DOI: 10.5943/mycosphere/8/1/10
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal activity, cytotoxicity and histone modifications induced by malformin A1 isolated from the marine-derived fungus Aspergillus tubingensis IFM 63452

Abstract: Malformin A1, a cyclic pentapeptide, was isolated from the marine-derived fungus Aspergillus tubingensis IFM 63452. The identity of the compound was established based on TOF-MS and 1 H NMR data. Malformin A1 exhibited trypanocidal activity against Trypanosoma congolense (IC50: 15.08 ng/mL). Interestingly, the compound was selective for T. congolense rendering a selectivity index value that ranged from 3.33 to 4.67. It also demonstrated cytotoxicity against HeLa (IC50: 50.15 ng/mL) and P388 (IC50: 70.38 ng/mL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This is of course expected, as the genus Trichoderma is widely isolated from the soil of different grassland and forest ecosystems [32,33], though it has also been isolated from the marine environment [34]. Some of the substrates colonized by many marine-derived fungi, including marine isolates of Trichoderma, were seagrasses and seaweeds [35][36][37], with many of these marine-derived fungal strains producing metabolites similar to those observed in terrestrial strains [38]. The successful colonization of many substrata by fungi could be attributed to its ability to degrade different carbon sources [39][40][41].…”
Section: Discussionmentioning
confidence: 87%
“…This is of course expected, as the genus Trichoderma is widely isolated from the soil of different grassland and forest ecosystems [32,33], though it has also been isolated from the marine environment [34]. Some of the substrates colonized by many marine-derived fungi, including marine isolates of Trichoderma, were seagrasses and seaweeds [35][36][37], with many of these marine-derived fungal strains producing metabolites similar to those observed in terrestrial strains [38]. The successful colonization of many substrata by fungi could be attributed to its ability to degrade different carbon sources [39][40][41].…”
Section: Discussionmentioning
confidence: 87%
“…Fungal endophytes recovered from a wide lineage of plants have been investigated for bioprospecting [ 2 , 20 , 21 , 22 , 23 ]. Particularly on gymnosperms, early studies have reported the production of secondary metabolites with strong antimicrobial activity [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In human colorectal cancer cells (SW480 and DKO1), invasive and oncogenic phenotypes were modified through p38 signaling pathway [ 300 ]. Recently, the marine-derived fungus A. tubingenesis also yielded MA 1 with significant cytotoxicity against HeLa (IC 50 = 9.48 nM) and P388 (IC 50 = 132.9 nM) cell lines [ 301 ]. Malformin A 1 is an early-discovered cyclic peptide with diverse biological properties and sufficient studies have demonstrated its bioactivities as well as mechanism of action.…”
Section: Fungi-derived Anticancer Cyclopeptidesmentioning
confidence: 99%